Temperature-resistant load-type wave-absorbing material and preparation and test method thereof
Through the specific composition of temperature-load-resistant absorbing materials and real-time testing methods, the problems of poor stability and lack of real-time testing of temperature-resistant absorbing materials in the prior art are solved, and the high loss and stability of the material at high temperatures are achieved. , meets the needs of TR components in active phased array radar systems.
Patent Information
- Application Number
- CN202411323778.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The existing temperature-resistant load-type wave absorbing materials have poor stability at high temperatures and low electromagnetic losses. The existing test methods are not real-time, making it difficult to meet the needs of TR components in active phased array radar systems.
Using specific compositions of temperature-resistant load-resistant absorbing materials, including electromagnetic wave absorbers, epoxy resins and curing agents, materials with high loss and stability are prepared through organic solvent dissolution and ball milling screening, and real-time testing is provided. Methods are used to monitor the magnetoelectric parameters of the material at high temperatures.
It achieves material stability and high electromagnetic loss in the range of 150-280°C, meets the application needs of TR components, and ensures the accuracy and applicability of material properties through real-time testing methods.
Smart Images

Figure CN119192776A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a temperature-resistant load-type absorbing material and a preparation and testing method thereof. Background Art
[0002] The application of absorbing materials is becoming more and more extensive. As a type of absorbing material, load-type absorbing materials can be used for the terminal and load of attenuators, coaxial lines or waveguide cavities; they can be used to reduce the Q value of the resonant cavity and eliminate unnecessary resonance. In addition, load-type absorbing materials with high temperature resistance and high loss characteristics can also be used in TR components in active phased array radar systems.
[0003] At present, China has done a lot of research work on absorbing materials and accumulated a lot of technical experience, but there are still shortcomings such as poor temperature stability, low electromagnetic loss, serious heat accumulation, and powdering after long-term high-temperature operation. No load-type absorbing materials that can better meet the needs of TR components have been produced.
[0004] Chinese patent CN116178891A discloses a method for preparing a high-temperature resistant loaded absorbing material. The invention uses mechanical stirring to directly pre-mix the absorbent coated with a coupling agent on the surface with epoxy resin, curing agent and accelerator to obtain a slurry. However, when the absorbent content is relatively high or the absorbent absorbs a large amount of oil, it is difficult to obtain a uniformly stirred slurry by direct mixing, so it is difficult to ensure that the absorbent surface is uniformly coated with epoxy resin and curing agent, which will eventually lead to the inability of various indicators of the loaded absorbing material to meet actual requirements. In addition, Chinese patent CN102351467A discloses a method for preparing an absorbing composite material for isolator loading. The invention uses a casting method to obtain a casting body. This method has the disadvantages of introducing air during casting and is not suitable for preparing high-solid content loaded materials.
[0005] In addition, the test method for temperature-resistant load-type absorbing materials generally requires testing their ability to attenuate electromagnetic waves at real-time temperatures. Currently, most tests of temperature resistance are not real-time, but the results of the test after heating to a set temperature and keeping it warm for a certain period of time, and then cooling to room temperature.
[0006] Therefore, it is of great significance to provide a load-type absorbing material with strong temperature resistance and stability and high electromagnetic loss and a preparation method thereof, as well as a test method that can test its electromagnetic wave attenuation ability in real time. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a temperature-resistant load-type absorbing material and its preparation and testing methods. The temperature-resistant load-type absorbing material provided by the present invention has excellent comprehensive performance, which can not only be used for the terminal and load of attenuators, coaxial lines or waveguide cavities, but also meet the application of TR components in active phased array radar systems. At the same time, the testing method of the load-type absorbing material provided by the present invention can solve the technical problems in the existing testing methods that the magnetoelectric parameters of the material at a certain temperature cannot be monitored in real time or the testing steps are cumbersome.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a temperature-resistant loaded absorbing material, wherein the temperature-resistant loaded absorbing material comprises the following components in weight percentage:
[0010] Electromagnetic wave absorber 70-95%
[0011] Epoxy resin 2.3-12%
[0012] Curing agent 2.7-18%;
[0013] The electromagnetic wave absorber includes Y2Fe 15 Any one of CrMo, Y2Co8Fe9, FeSiCr, carbonyl iron or FeNi, or a combination of at least two thereof.
[0014] The present invention achieves excellent comprehensive properties such as strong temperature resistance and stability (stable performance at 150-280°C) and high electromagnetic loss by specifically matching the components in the load-type absorbing material. The material can be used not only as a terminal and load of an attenuator, a coaxial line or a waveguide cavity, but also as a TR component in an active phased array radar system.
[0015] The high loss refers to the large attenuation capability of the absorbing material to electromagnetic waves.
[0016] The weight percentage of the electromagnetic wave absorber is 70-95%, for example, it can be 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90% or 92%.
[0017] The weight percentage of the epoxy resin is 2.3-12%, for example, it can be 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or 11%.
[0018] The weight percentage of the curing agent is 2.7-18%, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14% or 16%.
[0019] Preferably, the epoxy resin includes any one of phenolic resin, silicone resin, polyamide resin or cyanate resin, or a combination of at least two of them.
[0020] Preferably, the curing agent includes an amine curing agent or an acid anhydride curing agent.
[0021] Preferably, the amine curing agent includes any one of ethylenediamine, diethylenetriamine, polyetheramine, meta-xylylenediamine, diaminodiphenylmethane or diaminodiphenyl sulfone, or a combination of at least two thereof.
[0022] Preferably, the anhydride curing agent includes any one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or chlorohydric anhydride, or a combination of at least two thereof.
[0023] Preferably, the mass ratio of the epoxy resin to the curing agent is 1:(1-1.5), for example, it can be 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4 or 1:1.5, etc.
[0024] In the components of the heat-resistant supported absorbing material provided by the present invention, when the mass ratio of epoxy resin to curing agent is 1:(1-1.5), the supported absorbing material obtained has good mechanical properties and suitable hardness. When the mass ratio is higher than 1:1, the content of epoxy resin is high and the hardness of the supported absorbing material is low. When the mass ratio is lower than 1:1.5, the content of curing agent is high, the brittleness of the supported absorbing material is enhanced, and the mechanical properties such as tensile strength and flexural strength are sharply reduced.
[0025] In a second aspect, the present invention provides a method for preparing the temperature-resistant loaded absorbing material as described in the first aspect, the preparation method comprising the following steps:
[0026] S1, dissolving epoxy resin and curing agent in an organic solvent, mixing evenly, and then adding electromagnetic wave absorber, stirring and mixing to obtain a composite absorber;
[0027] S2, crushing and dispersing the composite absorbent in S1, and then screening it;
[0028] S3, compression molding the material after screening in S2 to obtain a green body;
[0029] S4, heating and curing the green body in S3, cutting and polishing to obtain the temperature-resistant load-type absorbing material.
[0030] Preferably, the organic solvent in step S1 includes any one of acetone, ethanol or n-hexane, or a combination of at least two of them.
[0031] In the preparation method of the load-type absorbing material provided by the present invention, the epoxy resin and the curing agent are first dissolved by an organic solvent, which can not only better increase the uniform mixing of the two with the electromagnetic wave absorber, so that the surface of the electromagnetic wave absorber can be evenly coated with the epoxy resin and the curing agent, but also greatly increase the content of the added absorbing agent, and can also improve the consistency and temperature resistance of the material while solving the problem of low material loss, so that the various indicators of the finally obtained load-type absorbing material can meet the actual requirements, and can not only be used for the terminal and load of the attenuator, coaxial line or waveguide cavity, but also meet the application of TR components in active phased array radar systems.
[0032] Preferably, the mass ratio of the organic solvent to the epoxy resin is (2-5):1, for example, it can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1.
[0033] Preferably, the stirring temperature in step S1 is 40-45°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C.
[0034] Preferably, the composite absorbent in step S1 is dry particles.
[0035] Preferably, the crushing and dispersing method in step S2 is ball milling using a ball mill.
[0036] Preferably, the rotation speed of the ball mill is 100-300 r / min, for example, it can be 100 r / min, 120 r / min, 150 r / min, 180 r / min, 200 r / min, 220 r / min, 250 r / min, 280 r / min or 300 r / min.
[0037] Preferably, the ball milling time is 1-5 h, for example, it can be 1.2 h, 1.5 h, 1.8 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 4.8 h.
[0038] Preferably, the screening process in step S2 is performed by using a vibrating screen.
[0039] Preferably, the sieve aperture of the screening is 60-100 mesh, for example, it can be 60 mesh, 70 mesh, 80 mesh, 90 mesh or 100 mesh.
[0040] Preferably, the pressure of the compression molding in step S3 is 5-10 t / cm 2 , for example, it can be 5t / cm 2 , 6t / cm 2 , 7t / cm 2 , 8t / cm 2 , 9t / cm2 or 10t / cm 2 wait.
[0041] Preferably, the compression molding in step S3 refers to putting the material into the hopper of the compression molding machine, the equipment automatically loads the material into the mold cavity, and then closes the mold, transmits pressure through hydraulic oil, and pressurizes to 5-10t / cm 2 Make the material dense and shaped.
[0042] Preferably, the heating and curing in step S4 is carried out in an oven.
[0043] Preferably, the heating and curing is performed in stages.
[0044] Preferably, the segmented heating and curing includes a first segment heating and curing, a second segment heating and curing, and a third segment heating and curing.
[0045] Preferably, the temperature of the first stage heating and curing is 80-100°C, for example, 82°C, 85°C, 88°C, 90°C, 92°C, 95°C or 98°C.
[0046] Preferably, the first stage of heating and curing time is 1.5-2.5 hours, for example, it can be 1.5 hours, 1.8 hours, 2.0 hours, 2.2 hours or 2.5 hours.
[0047] Preferably, the temperature of the second stage heating and curing is 110-130°C, for example, 112°C, 115°C, 120°C, 122°C, 125°C or 128°C.
[0048] Preferably, the second stage heating and curing time is 1.5-2.5 h, for example, 1.5 h, 1.8 h, 2.0 h, 2.2 h or 2.5 h.
[0049] Preferably, the temperature of the third stage heating and curing is 140-160°C, for example, 142°C, 145°C, 150°C, 152°C, 155°C or 158°C.
[0050] Preferably, the third stage of heating and curing lasts for 1.5-2.5 hours, for example, 1.5 hours, 1.8 hours, 2.0 hours, 2.2 hours or 2.5 hours.
[0051] In the present invention, the material is subjected to ball milling and screening, compression molding and segmented heating and curing processes in sequence, thereby solving the problems of uneven material organization and high porosity, and further enhancing the mechanical properties and density of the material. That is, the present invention can optimize the internal organization uniformity, density, pore defects, hardness, magnetoelectric parameters and mechanical properties of the load absorbing material through the mutual coordination of ball milling and screening, compression molding and segmented heating and curing processes, and obtain a load absorbing material with excellent performance, which can meet the application requirements of the TR component in the active phased array radar system for the high-loss load absorbing material with high temperature resistance, and the manufacturing method is simple and easy to operate, and is suitable for batch preparation.
[0052] Preferably, the method for preparing the temperature-resistant loaded absorbing material specifically comprises the following steps:
[0053] S1. Dissolve the epoxy resin and curing agent in an organic solvent, mix them evenly, continue to add the electromagnetic wave absorber, stir and mix at 40-45° C. to obtain a granular composite absorber;
[0054] S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 100-300r / min, and the ball-milling time is 1-5h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 60-100 mesh;
[0055] S3, put the material after screening in S2 into the hopper of the pressure forming machine, the equipment automatically puts the material into the mold cavity, then closes the mold, transmits pressure through hydraulic oil, and pressurizes to 5-10t / cm 2 Make the material compact and form to obtain a green body;
[0056] S4, placing the green body in S3 into an oven for segmented heating and curing, wherein the first segment is heated and cured at 80-100°C for 1.5-2.5h, the second segment is heated and cured at 110-130°C for 1.5-2.5h, and the third segment is heated and cured at 140-160°C for 1.5-2.5h. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
[0057] In a third aspect, the present invention provides a method for testing the temperature-resistant loaded absorbing material as described in the first aspect, the testing method comprising the following steps:
[0058] (1) Use the waveguide calibration kit to complete the two-port calibration according to the vector network analyzer system prompts;
[0059] (2) placing a sample of the loaded absorbing material as a test piece into the waveguide fixture;
[0060] (3) Place the waveguide fixture containing the test piece in the center of the heating area of the high-temperature furnace and secure it, then close the furnace cover;
[0061] (4) Using a vector network analyzer to test the magnetoelectric parameters of the loaded absorbing material at 25°C, and then setting a multi-stage program to control the rising temperature and holding time of the furnace to test the real-time magnetoelectric parameters of the loaded absorbing material at the set temperature;
[0062] (5) While the furnace is cooling down until it returns to 25°C, the real-time magnetoelectric parameters of the loaded absorbing material are tested.
[0063] Preferably, the thickness of the loaded absorbing material sample in step (2) is 1.5-2.5 mm, for example, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm or 2.4 mm.
[0064] Preferably, the size of the loaded absorbing material sample in step (2) is 2.2 cm in length and 1.1 cm in width.
[0065] Preferably, the inner wall of the high-temperature furnace in step (3) is provided with aluminum silicate fiber insulation material around it.
[0066] Preferably, the rising temperature of the furnace in step (4) is set to 25°C, 50°C, 100°C, 150°C and 200°C.
[0067] Preferably, the insulation time in step (4) is 5 minutes.
[0068] Preferably, the real-time magnetoelectric parameter test in step (4) refers to testing the magnetoelectric parameters of the loaded absorbing material once every 5 minutes.
[0069] Preferably, the real-time magnetoelectric parameter test in step (5) refers to testing the magnetoelectric parameters of the loaded absorbing material once every 5 minutes.
[0070] The testing method of the temperature-resistant loaded absorbing material provided by the present invention is simple, convenient and highly accurate, and can test the magnetoelectric parameters of the material at real-time temperature, and further obtain the attenuation coefficient of the material, thereby providing an intuitive and accurate basis for using the loaded absorbing material in the TR component of the active phased array radar system, and has high practicality.
[0071] Compared with the prior art, the present invention has at least the following beneficial effects:
[0072] (1) The high-temperature load absorbing material of the present invention has the advantages of strong temperature stability and high electromagnetic loss under the premise of high solid content, which well solves the problems of poor heat stability, low electromagnetic loss and serious heat accumulation in high solid content absorbing materials, and can better meet the application requirements in TR components;
[0073] (2) The preparation method of the temperature-resistant load absorbing material of the present invention can be better mixed with the electromagnetic wave absorber after the epoxy resin and the curing agent are dissolved in the organic solvent, and when mixed with the high oil absorption absorber or when preparing a high solid content load, it has more obvious advantages than the direct stirring and mixing method;
[0074] (3) The preparation method of the heat-resistant load absorbing material of the present invention subjects the composite absorber to ball milling, screening, compression molding and heating and curing processes, which can optimize the internal structure uniformity, density, pore defects, hardness, magnetoelectric parameters and mechanical properties of the load absorbing material, and obtain a load absorbing material with excellent performance, which can meet the application requirements of the TR component in the active phased array radar system for heat-resistant high-loss load absorbing materials, and the manufacturing method is simple and easy to operate, and is suitable for batch preparation;
[0075] (4) The testing method of the temperature-resistant high-loss load absorbing material provided by the present invention can test the magnetoelectric parameters of the material at real temperature and can truly reflect the performance of the material at a specific temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is a graph showing the change in real-time attenuation coefficient of the temperature-resistant high-loss load absorbing material prepared in Example 1 over frequency in a temperature cycle of 25°C-200°C-25°C in the X-band, wherein up is the rising temperature and down is the cooling temperature. DETAILED DESCRIPTION
[0077] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0078] The following raw material information is as follows:
[0079] Phenolic resin was purchased from Dongguan Yuanbang Electronic Materials Co., Ltd., 369A;
[0080] Silicone resin was purchased from Dongguan Yuanbang Electronic Materials Co., Ltd., RES-801;
[0081] Polyamide resin was purchased from Anhui Hongtai New Materials Co., Ltd., HY-16.
[0082] Example 1
[0083] This embodiment provides a temperature-resistant load-type absorbing material, which includes the following components in weight percentage:
[0084] Y2F 15 CrMo 95%
[0085] Silicone resin 2.3%
[0086] Methylhexahydrophthalic anhydride 2.7%;
[0087] The preparation method of the temperature-resistant loaded absorbing material is as follows:
[0088] S1. Dissolve 16g of silicone resin and 19g of methyl hexahydrophthalic anhydride in 70mL of acetone, mix well and add to the rubber mixer. Continue to add 665g of Y2Fe 15 CrMo, stirred and mixed at 40°C to obtain a granular composite absorbent;
[0089] S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 150r / min, and the ball-milling time is 2h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 100 mesh;
[0090] S3: Put the screened material from S2 into the hopper of the pressure forming machine. The equipment automatically puts the material into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes it to 5t / cm 2 Make the material compact and form to obtain a green body;
[0091] S4, placing the green body in S3 into an oven for segmented heating and curing, wherein the first segment is heated and cured at 90°C for 2h, the second segment is heated and cured at 120°C for 2h, and the third segment is heated and cured at 150°C for 2h. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
[0092] Example 2
[0093] This embodiment provides a temperature-resistant load-type absorbing material, which includes the following components in weight percentage:
[0094] Y2Co8Fe9 70%
[0095] Phenolic resin 12%
[0096] Methyltetrahydrophthalic anhydride 18%;
[0097] The preparation method of the temperature-resistant loaded absorbing material is as follows:
[0098] S1, 84g of phenolic resin and 126g of methyltetrahydrophthalic anhydride were dissolved in 255mL of n-hexane, mixed evenly and added to a rubber mixer, and 490g of Y2Co8Fe9 was added, and stirred and mixed at 42°C to obtain a granular composite absorbent;
[0099] S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 200r / min, and the ball-milling time is 2h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 60 mesh;
[0100] S3: Put the screened material from S2 into the hopper of the pressure forming machine. The equipment automatically puts the material into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes it to 7t / cm 2 Make the material compact and form to obtain a green body;
[0101] S4, placing the green body in S3 into an oven for segmented heating and curing, wherein the first segment of heating and curing is performed at 80°C for 2.5 hours, the second segment of heating and curing is performed at 110°C for 2.5 hours, and the third segment of heating and curing is performed at 140°C for 2.5 hours. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
[0102] Example 3
[0103] This embodiment provides a temperature-resistant load-type absorbing material, which includes the following components in weight percentage:
[0104] FeSiCr 82%
[0105] Polyamide resin 9%
[0106] Chloroanhydride 9%;
[0107] The preparation method of the temperature-resistant loaded absorbing material is as follows:
[0108] S1, 63g polyamide resin and 63g chlorohydride are dissolved in 399mL ethanol, mixed evenly and added into a rubber mixer, and 574g FeSiCr is added, and stirred and mixed at 45°C to obtain a granular composite absorbent;
[0109] S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 250r / min, and the ball-milling time is 1h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 80 mesh;
[0110] S3: Put the screened material from S2 into the hopper of the pressure forming machine. The equipment automatically puts the material into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes it to 10t / cm 2 Make the material compact and form to obtain a green body;
[0111] S4, placing the green body in S3 into an oven for segmented heating and curing, wherein the first segment of heating and curing is performed at 100°C for 1.5 hours, the second segment of heating and curing is performed at 130°C for 1.5 hours, and the third segment of heating and curing is performed at 160°C for 1.5 hours. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
[0112] Example 4
[0113] This embodiment provides a temperature-resistant load-type absorbing material, which differs from Example 3 in that the weight percentage of polyamide resin is adjusted to 7%, the weight percentage of chlorohydric anhydride is adjusted to 11%, and the other components, contents and preparation methods are the same as those in Example 3.
[0114] Example 5
[0115] This embodiment provides a temperature-resistant load-type absorbing material, which differs from Example 3 in that the weight percentage of polyamide resin is adjusted to 9.5%, the weight percentage of chlorohydric anhydride is adjusted to 8.5%, and the other components, contents and preparation methods are the same as those in Example 3.
[0116] Comparative Example 1
[0117] This comparative example provides a temperature-resistant load-type absorbing material, which differs from Example 1 in that the weight percentage of the silicone resin is adjusted to 1.8%, the weight percentage of methylhexahydrophthalic anhydride is adjusted to 3.2%, and the other components, contents and preparation methods are the same as those in Example 1.
[0118] Comparative Example 2
[0119] This comparative example provides a temperature-resistant load-type absorbing material, which differs from Example 1 in that the weight percentage of the silicone resin is adjusted to 3%, the weight percentage of methylhexahydrophthalic anhydride is adjusted to 2%, and the other components, contents and preparation methods are the same as those in Example 1.
[0120] Comparative Example 3
[0121] This comparative example provides a supported absorbing material, which is different from Example 1 in that the preparation method of the supported absorbing material is different. The preparation method of this example is as follows:
[0122] S1, 16g of silicone resin, 19g of methyl hexahydrophthalic anhydride and 665g of Y2Fe 15 CrMo is mechanically stirred and mixed for 30 minutes to obtain a first mixture;
[0123] S2, the first mixture in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 150r / min, and the ball-milling time is 2h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 100 mesh;
[0124] S3: Put the screened material from S2 into the hopper of the pressure forming machine. The equipment automatically puts the material into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes it to 5t / cm 2 Make the material compact and form to obtain a green body;
[0125] S4, placing the green body in S3 into an oven for segmented heating and curing, wherein the first segment is heated and cured at 90°C for 2h, the second segment is heated and cured at 120°C for 2h, and the third segment is heated and cured at 150°C for 2h. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
[0126] Comparative Example 4
[0127] This comparative example provides a supported absorbing material, which is different from Example 1 in that the preparation method of the supported absorbing material is different. The preparation method of this example is as follows:
[0128] S1. Dissolve 16g of silicone resin and 19g of methyl hexahydrophthalic anhydride in 70mL of acetone, mix well and add to the rubber mixer. Continue to add 665g of Y2Fe 15 CrMo, stirred and mixed at 40°C to obtain a granular composite absorbent;
[0129] S2. Put the composite absorbent in S1 into the hopper of the pressure molding machine. The equipment automatically puts the composite absorbent into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes to 5t / cm 2 Make the material compact and form to obtain a green body;
[0130] S3, placing the green body in S2 into an oven for segmented heating and curing, wherein the first segment is heated and cured at 90°C for 2h, the second segment is heated and cured at 120°C for 2h, and the third segment is heated and cured at 150°C for 2h. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
[0131] Comparative Example 5
[0132] This comparative example provides a supported absorbing material, which is different from Example 1 in that the preparation method of the supported absorbing material is different. The preparation method of this example is as follows:
[0133] S1. Dissolve 16g of silicone resin and 19g of methyl hexahydrophthalic anhydride in 70mL of acetone, mix well and add to the rubber mixer. Continue to add 665g of Y2Fe 15 CrMo, stirred and mixed at 40°C to obtain a granular composite absorbent;
[0134] S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 150r / min, and the ball-milling time is 2h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 100 mesh;
[0135] S3: Put the screened material from S2 into the hopper of the pressure forming machine. The equipment automatically puts the material into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes it to 5t / cm 2 Make the material compact and form to obtain a green body;
[0136] S4, placing the green body in S2 into an oven for heating and curing at 120° C. for 6 hours. After the heating and curing is completed, cutting and polishing are performed to obtain the temperature-resistant load-type absorbing material.
[0137] Comparative Example 6
[0138] This comparative example provides a supported absorbing material, which is different from Example 1 in that the preparation method of the supported absorbing material is different. The preparation method of this example is as follows:
[0139] S1. Dissolve 16g of silicone resin and 19g of methyl hexahydrophthalic anhydride in 70mL of acetone, mix well and add to the rubber mixer. Continue to add 665g of Y2Fe 15 CrMo, stirred and mixed at 40°C to obtain a granular composite absorbent;
[0140] S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 150r / min, and the ball-milling time is 2h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 100 mesh;
[0141] S3: Put the screened material from S2 into the hopper of the pressure forming machine. The equipment automatically puts the material into a square mold cavity with a side length of 12 cm, then closes the mold, transmits pressure through hydraulic oil, and pressurizes it to 5t / cm 2 Make the material compact and form to obtain a green body;
[0142] S4, placing the green body in S2 into an oven for heating and curing at 150° C. for 6 hours. After the heating and curing is completed, cutting and polishing are performed to obtain the temperature-resistant load-type absorbing material.
[0143] Comparative Example 7
[0144] This comparative example provides a supported absorbing material, which differs from Example 1 in that the preparation method of the supported absorbing material is different. The preparation method of this comparative example is as follows:
[0145] 665g Y2Fe 15 After CrMo and 135g of anhydrous ethanol were mixed and stirred for 30 minutes, 16g of silicone resin and 19g of curing agent were added, and vacuum stirring and degassing were performed at 120°C. When no bubbles were observed with the naked eye, casting was performed. The mold was preheated with a release agent (boron nitride) and 150°C in advance, and the cast body was heated and cured at 120°C for 3h and 150°C for 3h. The cast body was demoulded, and finally cut and polished to obtain the supported absorbing material.
[0146] Test Case
[0147] This test example provides a test method for a temperature-resistant load-type absorbing material, including the following steps:
[0148] (1) Use the waveguide calibration kit to complete the two-port calibration according to the vector network analyzer system prompts;
[0149] (2) The loaded absorbing material in Example 1 was processed into a sample with a length of 2.2 cm, a width of 1.1 cm, and a thickness of 2 mm and placed in the waveguide fixture as a test piece;
[0150] (3) Place the waveguide fixture containing the test piece in the center of the heating area of the high-temperature furnace and secure it, then close the furnace cover;
[0151] (4) The magnetoelectric parameters of the loaded absorbing material at 25°C were first tested, and then the real-time magnetoelectric parameters were tested after being kept at 50°C, 100°C, 150°C and 200°C for 5 minutes. Finally, when the heating furnace program was stopped and the temperature was lowered, the real-time magnetoelectric parameters were tested again at 150°C, 100°C, 50°C and when cooled to 25°C. Finally, the attenuation coefficient of the loaded absorbing material in the X-band (8.2-12.4 GHz) was obtained by calculation.
[0152] like Figure 1 As shown, the loaded absorbing material obtained in Example 1 has a large attenuation coefficient and small fluctuation within the temperature cycle of 25°C-200°C-25°C in the X-band, indicating that the material has good temperature resistance and high attenuation performance.
[0153] The performance tests of Examples 1-5 and Comparative Examples 1-7 were carried out, and the specific test methods are as follows:
[0154] (1) Density test: Place the loaded absorbing material on a density meter and use the drainage method to test the density of the material;
[0155] (2) Hardness test: The hardness of the material is tested using a Shore hardness tester;
[0156] (3) Bending strength and tensile strength test: Use a universal testing machine for testing;
[0157] (4) Service temperature test: Place the sample in a box furnace for service temperature test;
[0158] (5) Magnetic loss test: Use a vector network analyzer to test and calculate the magnetic loss at 12.4 GHz.
[0159] The test results are shown in Table 1:
[0160] Table 1
[0161]
[0162] The test results show that:
[0163] (1) It can be seen from Examples 1-5 that the present invention can not only realize the preparation of a high solid content (not less than 70%) supported absorbing material through a specific preparation method, but also the prepared supported absorbing material has the advantages of good mechanical properties, strong temperature stability and high electromagnetic loss.
[0164] (2) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the present invention can significantly improve the mechanical properties such as bending strength and tensile strength of the load absorbing material by specifically matching the content of each component in the load absorbing material. When the content of the epoxy resin or the curing agent exceeds the specific range of the present invention, its mechanical properties, temperature resistance and magnetic loss are all reduced.
[0165] (3) By comparing Example 1 with Comparative Example 3, it can be seen that in the preparation method of the present invention, after the epoxy resin and the curing agent are dissolved in an organic solvent, they can be better mixed with the electromagnetic wave absorber, and when mixed with a high oil absorption absorber or when preparing a high solid content load, it has a more obvious advantage than the direct stirring and mixing method.
[0166] (4) It can be seen from Example 1 and Comparative Examples 4-7 that the preparation method provided by the present invention can optimize the internal structure uniformity, density, pore defects, etc. of the load absorbing material by subjecting the material to ball milling screening, compression molding and segmented heating and curing steps, so that the obtained material has better effects in terms of hardness, magnetoelectric parameters, mechanical properties and temperature resistance, that is, a load absorbing material with excellent comprehensive performance is obtained, which can meet the application requirements of the TR component in the active phased array radar system for the high-loss load absorbing material with high temperature resistance, and the preparation method is simple and easy to operate, and is suitable for mass production.
[0167] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A temperature-resistant load-type absorbing material, characterized in that: The temperature-resistant load-type absorbing material comprises the following components in weight percentage: Electromagnetic wave absorber 70-95% Epoxy resin 2.3-12% Curing agent 2.7-18%; The electromagnetic wave absorber includes Y2Fe 15 Any one of CrMo, Y2Co8Fe9, FeSiCr, carbonyl iron or FeNi, or a combination of at least two thereof.
2. The temperature-resistant loaded absorbing material according to claim 1, characterized in that: The epoxy resin includes any one of phenolic resin, silicone resin, polyamide resin or cyanate resin or a combination of at least two thereof; Preferably, the curing agent includes an amine curing agent or an acid anhydride curing agent; Preferably, the amine curing agent includes any one or a combination of at least two of ethylenediamine, diethylenetriamine, polyetheramine, m-phenylenediamine, diaminodiphenylmethane or diaminodiphenyl sulfone; Preferably, the anhydride curing agent includes any one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or chlorohydric anhydride, or a combination of at least two thereof.
3. The temperature-resistant loaded absorbing material according to claim 1 or 2, characterized in that: The mass ratio of the epoxy resin to the curing agent is 1:(1-1.5).
4. A method for preparing a temperature-resistant loaded absorbing material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1, dissolving epoxy resin and curing agent in an organic solvent, mixing evenly, and then adding electromagnetic wave absorber, stirring and mixing to obtain a composite absorber; S2, crushing and dispersing the composite absorbent in S1, and then screening it; S3, compression molding the material after screening in S2 to obtain a green body; S4, heating and curing the green body in S3, cutting and polishing to obtain the temperature-resistant load-type absorbing material.
5. The preparation method according to claim 4, characterized in that: The organic solvent in step S1 includes any one of acetone, ethanol or n-hexane or a combination of at least two thereof; Preferably, the mass ratio of the organic solvent to the epoxy resin is (2-5):1; Preferably, the stirring temperature in step S1 is 40-45°C; Preferably, the composite absorbent in step S1 is dry particles.
6. The preparation method according to claim 4 or 5, characterized in that: The crushing and dispersing method in step S2 is ball milling; Preferably, the rotation speed of the ball mill is 100-300r / min; Preferably, the ball milling time is 1-5h; Preferably, the screening process in step S2 is performed by using a vibrating screen machine; Preferably, the sieve mesh size is 60-100 mesh.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The pressure of the compression molding in step S3 is 5-10t / cm 2 ; Preferably, the compression molding in step S3 refers to putting the material into the hopper of the compression molding machine, the equipment automatically loads the material into the mold cavity, and then closes the mold, transmits pressure through hydraulic oil, and pressurizes to 5-10t / cm 2 Make the material dense and shaped.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The heating and curing in step S4 is carried out in an oven; Preferably, the heating and curing method is segmented heating and curing; Preferably, the segmented heating and curing includes a first segment heating and curing, a second segment heating and curing, and a third segment heating and curing; Preferably, the temperature of the first stage heating and curing is 80-100°C; Preferably, the first stage of heating and curing time is 1.5-2.5h; Preferably, the temperature of the second stage heating and curing is 110-130°C; Preferably, the second stage of heating and curing takes 1.5-2.5 hours; Preferably, the temperature of the third stage heating and curing is 140-160°C; Preferably, the third stage of heating and curing lasts for 1.5-2.5 hours.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method specifically comprises the following steps: S1. Dissolve the epoxy resin and curing agent in an organic solvent, mix them evenly, continue to add the electromagnetic wave absorber, stir and mix at 40-45° C. to obtain a granular composite absorber; S2, the composite absorbent in S1 is firstly ball-milled and dispersed in a ball mill, the ball-milling speed is 100-300r / min, and the ball-milling time is 1-5h; then the crushed and dispersed material is added to a vibrating screen for screening, and the sieve aperture of the screening is 60-100 mesh; S3, put the material after screening in S2 into the hopper of the pressure forming machine, the equipment automatically puts the material into the mold cavity, then closes the mold, transmits pressure through hydraulic oil, and pressurizes to 5-10t / cm 2 Make the material compact and form to obtain a green body; S4, placing the green body in S3 into an oven for segmented heating and curing, wherein the first segment is heated and cured at 80-100°C for 1.5-2.5h, the second segment is heated and cured at 110-130°C for 1.5-2.5h, and the third segment is heated and cured at 140-160°C for 1.5-2.5h. After the heating and curing is completed, the green body is cut and polished to obtain the temperature-resistant load-type absorbing material.
10. A method for testing the temperature-resistant loaded absorbing material according to claim 1 or 2, characterized in that: The test method comprises the following steps: (1) Use the waveguide calibration kit to complete the two-port calibration according to the vector network analyzer system prompts; (2) placing a sample of the loaded absorbing material as a test piece into a waveguide fixture; (3) Place the waveguide fixture containing the test piece in the center of the heating area of the high-temperature furnace and secure it, then close the furnace cover; (4) Using a vector network analyzer to test the magnetoelectric parameters of the loaded absorbing material at 25°C, and then setting a multi-stage program to control the rising temperature and holding time of the furnace to test the real-time magnetoelectric parameters of the loaded absorbing material at the set temperature; (5) While the furnace is cooling down until it returns to 25°C, test the real-time magnetoelectric parameters of the loaded absorbing material; Preferably, the thickness of the supported absorbing material sample in step (2) is 1.5 to 2.5 mm; Preferably, the size of the loaded absorbing material sample in step (2) is 2.2 cm in length and 1.1 cm in width; Preferably, the inner wall of the high temperature furnace in step (3) is provided with aluminum silicate fiber insulation material around the inner wall of the furnace body; Preferably, the rising temperature of the furnace in step (4) is set to 25°C, 50°C, 100°C, 150°C and 200°C; Preferably, the insulation time in step (4) is 1-10 min; Preferably, the real-time magnetoelectric parameter test in step (4) refers to testing the magnetoelectric parameters of the loaded absorbing material once every 5 minutes; Preferably, the real-time magnetoelectric parameter test in step (5) refers to testing the magnetoelectric parameters of the loaded absorbing material once every 5 minutes.
